2018
DOI: 10.1039/c7ob02840g
|View full text |Cite
|
Sign up to set email alerts
|

Mannich reaction of trifluoroacetaldehyde hydrazones: a useful entry to trifluoromethyl substituted heterocycles

Abstract: NH-aryl hydrazones derived from trifluoroacetaldehyde hemiacetal may be involved in efficient Mannich type reactions with formaldehydes and aromatic aldehydes. The resulting hydrazones are useful building blocks for the preparation of trifluoromethyl substituted heterocycles as shown by a straightforward preparation of 1,2-diazine derivatives under heating with β-ketoesters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…El Kaim and Jia reported a Mannich-type reaction of trifluoroacetaldehyde hydrazones with formaldehyde and aromatic alde- hydes to obtain valuable starting materials for the generation of other trifluoromethyl-substituted heterocycles. The study demonstrated that the electron-withdrawing property of the trifluoromethyl group is key to this coupling reaction [45] (Scheme 7).…”
Section: Review Trifluoroacetaldehyde Hydrazonesmentioning
confidence: 98%
“…El Kaim and Jia reported a Mannich-type reaction of trifluoroacetaldehyde hydrazones with formaldehyde and aromatic alde- hydes to obtain valuable starting materials for the generation of other trifluoromethyl-substituted heterocycles. The study demonstrated that the electron-withdrawing property of the trifluoromethyl group is key to this coupling reaction [45] (Scheme 7).…”
Section: Review Trifluoroacetaldehyde Hydrazonesmentioning
confidence: 98%
“…[2] Furthermore, functionalized hydrazones can also serve as valuable building blocks to construct various functional molecules in synthetic chemistry. [3] Consequently, some functionalized hydrazones such as acyl, [4] α-fluoroalkylated, [5] sulfonyl [6] and phosphinic hydrazones [7,8] have been thereby synthesized through various synthetic transformations. Among them, phosphinic hydrazones have received the special attention due to their interesting chemical and biological activities 8 and important synthetic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrazones have emerged as an important class of compounds that serve as versatile intermediates in organic synthesis because of their multiple reactivities attributed to their unique structure . One of the most important features of hydrazones is the ambiphilic nature of the azomethine carbon (Scheme a). ,, Because of the intrinsic polarization of the CN bond similar to that of the carbonyl group, hydrazones have been employed as electrophiles in reactions with nucleophiles such as organometallic reagents .…”
mentioning
confidence: 99%